Disease Associated with Equine Coronavirus Infection and High Case Fatality Rate. (15th October 2014) - Fielding, C.L.; Higgins, J.K.; Higgins, J.C.; McIntosh, S.; Scott, E.; Giannitti, F.; Mete, A.; Pusterla, N.
<x xml:space="preserve">Abstract</x> Background Equine coronavirus (ECoV) is associated with clinical disease in adult horses. Outbreaks are associated with a low case fatality rate and a small number of animals with signs of encephalopathic disease are described. Objectives The aim of this study is to describe the epidemiological and clinical features of two outbreaks of ECoV infection that were associated with an high case fatality rate. Animals 14 miniature horses and 1 miniature donkey testing fecal positive for ECoV from two related disease outbreaks. Methods Retrospective study describing the epidemiological findings, clinicopathological findings, and fecal viral load from affected horses. Results In EcoV positive horses, 27% (4/15) of the animals died or were euthanized. Severe hyperammonemia (677 μmol/L, reference range ≤60 μmol/L) was identified in one animal with signs of encephalopathic disease that subsequently died. Fecal viral load (ECoV genome equivalents per gram of feces) was significantly higher in the nonsurvivors compared to animals that survived (P = .02). Conclusions and Clinical Importance Equine coronavirus had a higher case fatality rate in this group of miniature horses than previously reported in other outbreaks of varying breeds. Hyperammonemia could contribute to signs of encephalopathic disease, and the fecal viral load might be of prognostic value in affected horses.